Perspektif Guru dan Siswa terhadap Pelaksanaan PjBL dengan Pendekatan Experiental Learning pada Pembelajaran IPA - Rahmahabibty, Corina Destya; Chamisijatin, Lise; Zaenab, Siti (Journal of Natural Sciences, 2025)
This study aims to determine the implementation of Project Based Learning through experiential learning, teacher and student perspectives on the implementation of learning, and to determine the achievement of student competencies. The method used is qualitative with systematic observation instruments, non-systematic observations, surveys to students, and interviews with teachers. The results of the study showed that the perspectives of teachers and students were considered positive. The teacher's perspective stated that students were involved in learning that encouraged student activeness so that real experiences were formed. While the student perspective, it was conveyed that they felt excited, happy, motivated, and experienced direct involvement that allowed understanding of the material to be achieved. The implementation of learning had an impact on the achievement of student competencies with the results of an increase in knowledge scores (the average increased from 59.03 to 77.55), as well as an increase in attitude and skill scores, with an average skill reaching 83.33 and the majority of students achieving A and B scores.